Cover Feature: Engineering Active Sites in Three‐Dimensional Hierarchically Porous Graphene‐Like Carbon with Co and N‐Doped Carbon for High‐Performance Zinc‐Air Battery (ChemElectroChem 21/2021). Issue 21 (30th September 2021) - Bera, Raj Kumar; Park, Hongjun; Ryoo, Ryong
Abstract : The Cover Feature illustrates the high accessibility of active sites through the pores of three‐dimensional graphene‐like carbon for oxygen reduction and evolution reactions, which are the key processes in a Zn‐air battery. More information can be found in the Article by R. K. Bera, H. Park and R. Ryoo .